CHALLENGES AND PRECONDITIONS OF DIGITAL TRANSFORMATION IN FINANCIAL MANAGEMENT - Буяк, Лілія (SWorldJournal, 2024)
Ukraine has all the necessary resources and infrastructure potential for effective implementation of digital transformation and transition to digitisation. However, there are difficulties that make it difficult to fully exploit this potential. One such pr